Relationship Between the Practices of Learning Organization and Teacher Leadership at Indigenous Primary Schools of Kuala Langat District, Selangor, Malaysia - Saraswathy Kullan; Mahaliza Mansor (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2020)
The main focus of this study was to (1) identify the level of the practices of learning organization, (2) identify the level of teachers’ leadership, and (3) determine the relationship between practices of learning organization and teacher leadership. The theoretical framework of both Watkins and Marsick (1999) and Katzenmeyer and Moller (2009) were modified to form the conceptual framework of the study. The data were collected through questionnaires distributed to 72 teachers which were randomly selected from six Indigenous Primary Schools of Kuala Langat District, Selangor. The study was a quantitative research. The data collected was analyzed using descriptive and inferential statistics using the SPSS IBM Version 23.0 software. The results showed that the practices of learning organization by teachers recorded a high level of mean value at 3.87 and at 4.05 for teacher leadership. There was a moderate, positive and significant relationship between practices of learning organization and teacher leadership (r = 0.699, p0.01). This finding promotes practices of learning organization in schools which may lead to positive changes in teacher leadership. The implication of the study is the practices of learning organization should be practised at individuals, teams and organization levels in schools to improve the leadership skills of teachers through learning continuously.